Research and Development of Effects of Asphaltene Deposition in Tight Oil Reservoirs on CO2-EOR and CO2 Storage - Wang, Zhiyuan; Liu, Shaoqing; Hou, Wenlong (International Journal of Electric Power and Energy Studies, 2024)
CO2 injection can improve oil recovery significantly in tight oil reservoirs, in addition, CO2 injection after the use and storage reduce the amount of emissions into the atmosphere, so as to achieve the effect of emission reduction. However, in the process of production and storage, CO2 will interact with crude oil, formation water and rocks and minerals in the reservoir and react, thus changing the reservoir balance and fluid physical properties, resulting in solid phase deposition. Asphaltene deposits have a significant impact on the reservoir, especially on tight reservoirs.In this paper, The effects of asphaltene deposition caused by CO2 injection on oil recovery and CO2 sequestration in tight reservoirs were studied, and the research progress in this field is summarized and prospected. This study can provide reference for the development of tight oil reservoir and promote the development of tight oil recovery technology.